2018
DOI: 10.3390/ijerph15122856
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Free Press and Under-Reporting of Non-Fatal Occupational Injuries with Data from Representative National Indicators, 2015: Focusing on the Lethality Rate of Occupational Injuries among 39 Countries

Abstract: The epidemiology of occupational injuries is reported worldwide, but suspicions of under-reporting prevail, probably associated with free press. We examined the association between freedom of the press and lethality rate of occupational injuries based on the most comprehensive International Labour Organization database on labour statistics (ILOSTAT) among 39 countries. The occupational injury indices, national indicators, and information on freedom of the press in 2015 were sourced from ILOSTAT, World Bank ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Heinrich’s law has also supported the results of this research as Heinrich’s law categorized 0.3% accidents as having majorly injured the victim, 8.8% having been minorly injured, and 90.9% having no injuries. According to this pre-mentioned rule, the ratio between work accidents and injuries and fatal accidents and injuries comparatively increases at the same rate [ 53 ]. The short-run causality test shows unidirectional causality between work accident and cause-3 with a first difference at a 10% level of significance.…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich’s law has also supported the results of this research as Heinrich’s law categorized 0.3% accidents as having majorly injured the victim, 8.8% having been minorly injured, and 90.9% having no injuries. According to this pre-mentioned rule, the ratio between work accidents and injuries and fatal accidents and injuries comparatively increases at the same rate [ 53 ]. The short-run causality test shows unidirectional causality between work accident and cause-3 with a first difference at a 10% level of significance.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational accidents are a major public health challenge [ 1 ]. Although surveillance systems have been constructed to monitor the mortality and morbidity of occupational accidents, the surveillance data may be inaccurate due to underreporting or covering up of injuries and illnesses [ 6 , 19 ]. This impedes proper evaluation of the magnitude of health and safety problems in the workplace, which reduces protection of workers from workplace hazards, identification of risks, and implementation of needed interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the employers are not obliged to report the occupational injuries to authorities if the cost of the worker’s injury is paid directly by employer up until 2014 when a law on employer reporting of industrial accidents was put into place. Previous ecological studies among countries revealed that there may be under-reporting of occupational injuries, especially non-fatal occupational injuries 26 27. In addition, injuries caused by commuting accidents and injuries in daily life by job-related lifestyle behaviours, fatigue or psychological and physical problems were not reported in the database of worker's compensation insurance, although these injuries resulted from indirect effects of workers’ jobs.…”
Section: Discussionmentioning
confidence: 99%